Análise multivariada de microbacias em relação ao tipo de solo - Campos, Sérgio [UNESP]; Pissarra, Teresa Cristina Tarle [UNESP]; Rodrigues, Flavia Mazzer [UNESP]; Barros, Zacarias Xavier de [UNESP]; Ribeiro, Fernanda Leite (My University, 2010)
The objective of this work was to study the dimensional parameters of the drainage net using 12 third-order ramification hydrological watersheds: 4 watersheds per soil unit (LVA, RL and RQ). The soil distinction was realized using ''t'' test to verify the orthogonal contrast among three soil averages and the grouping analysis and mean components. The results showed that the multivariance analysis was not able to discriminate three soils using the dimensional analysis. The t test of this isolated variable allowed discriminating RQ soil from LVA and RL soil units; but it was not sensitive to discriminate the LVA soil and RL unit.

Este trabalho teve como objetivo analisar os parâmetros dimensionais da rede de drenagem através de 12 microbacias de 3a ordem de ramificação, sendo 4 microbacias por unidade de solo (LVA, RL e RQ). A distinção dos solos foi realizada através do teste t para verificação dos contrastes ortogonais entre as médias dos três solos e da análise de agrupamentos e de componentes principais. Os resultados permitiram concluir que a análise multivariada não foi eficiente na discriminação dos três solos através das variáveis dimensionais. Essas variáveis isoladamente através do teste t permitiram uma diferenciação entre o solo RQ e as unidades LVA e RL, porém não foram sensíveis para os solos LVA e RL.
Watershed multivariance analysis in relation to soil type
Keywords: Grouping; Multivariance analysis; Soil; Watershed; drainage; multivariate analysis; soil type; soil water; watershed